RETRACTED: Optimizing geothermal brine for balneological use: An integrated study of health, engineering, social, and economic dimesion - Naufal Fabianito Assariy; Arief Putra Pratama (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2025)
The Editorial Board of Journal of Innovation Materials, Energy, and Sustainable Engineering hereby retracts the article entitled “Optimizing geothermal brine for balneological use: An integrated study of health, engineering, social, and economic dimesion”, published in Vol. 3, No. 1, 2025 and accessible at https://journal-iasssf.com/index.php/JIMESE/article/view/2108. This decision follows confirmation of significant similarity with a previously prepared work by another research team, which had been presented at the IIGCE 2024 Conference. Although the earlier work was not formally published at the time of submission, data from that study were reused without proper authorization. The matter was reported to the Editorial Board in August 2025 and verified through internal review. At the request of the authors and in accordance with publication ethics, the Editorial Board has agreed to retract the article to maintain academic integrity and prevent redundant publication. We sincerely apologize to our readers, reviewers, and the wider academic community for any inconvenience caused.